A validated multi-channel electrochemical immunoassay for rapid fumonisin B1 determination in cereal samples1. Issue 9 (7th May 2015) - Ezquerra, Alba; Vidal, Juan C.; Bonel, Laura; Castillo, Juan R.
<x xml:space="preserve">Abstract</x> Fumonisin mycotoxins are natural contaminants of cereals mostly found in maize samples.